DISSOLUTION ENHANCEMENT OF SEROQUEL BY SOLID DISPERSION TECHNIQUES - Mohanty, Sangeeta; Pal, Abhisek (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Seroquel is an antipsychotic drug with plasma half-life of 6 hrs and poor oral bioavailability (9%) due to extensive first-pass metabolism. A present work is an attempt to improve oral bioavailability of seroquel by solid dispersions (SDs) (to improve the aqueous solubility and dissolution rate) so as to facilitate faster onset of action. Seroquel is a biopharmaceutical classification system Class II drug having low solubility (1.28 µg/ml). Methods: In the present investigation, an attempt was made to prepare SD with water-soluble carriers like polyethylene glycol (PEG 6000) PEG 6000 and PEG 4000. The SDs were prepared by melting method and physical mixing method by using PEG 6000 and PEG 4000 in the ratio 1:1, 1:3 and 1:5 respectfully. The prepared dispersions were evaluated for their physicochemical and dissolution characteristics. All the dispersions were easy to prepare, and the powder mass obtained in various formulations were free flowing under dry conditions. Physicochemical properties of the products were characterized by Fourier infrared spectroscopy which reveals that there is no interaction between drug and polymer. In vitro dissolution profiles of Seroquel formulations of physical mixtures (PMs) and melting methods were studied using Lab India Disso 2000 dissolution apparatus employing paddle method. 500 ml of 6.2 phosphate buffer was used as dissolution medium maintained at 37±0.50°C, and the stirrer rotation was kept at 50 rpm. Aliquots were withdrawn at different time intervals and measured for the absorbance for Seroquel at 244 nm using ultra violet-visible spectrophotometer with a reference to suitably constructed standard plot. Results and Discussions: Mixture of drug:PEG 6000 in (1:3) ratio prepared by melting method gives the highest drug release (93.55%) than PM (88.12%) and pure drug (39.75%) in 60 minutes. The dissolution of all the preparation follows Higuchi order kinetics. Conclusion: It is concluded that in melting method, due to the fineness, amorphous state of the drug, particle size reduction and absence of aggregation, dissolution rate increases but in PMs only a marginal increase in dissolution rate because the size reduction process is not effective. Keywords: Dissolution, Solid dispersion, Seroquel.